Product market competition and the value of corporate cash: Evidence from trade liberalization - Alimov, Azizjon (Journal of Corporate Finance, 2014)
This paper uses the 1989 Canada–U.S. Free Trade Agreement as a source of exogenous variation in product markets to establish the impact of increased competition on the market valuation of corporate cash reserves. I find that the trade liberalization leads to a significant increase in the value of cash for firms experiencing a larger shock to their competitive environment. The impact of the trade liberalization is stronger among firms that face greater risk of losing investment opportunities to rivals. I also show that these inferences about the valuation effect of competition apply more broadly to a large sample of firms.